Effects of Supplementary Pensions on Economy - Poškutė, Virginija (Ekonomika, 1998)
Introduction of supplementary pension schemes is very much advocated at present in Lithuania. It is believed that newly established pension funds will provide some solutions to problems that the public pension system is facing in Lithuania, and at the same time, will help to improve some economic indicators of the country. This is often done by giving examples of the successful performance of pension funds in other countries. Presenting the advantages of such schemes without considering possible negative effects of the schemes is misleading. Therefore this paper provides an analysis in order to illustrate that the introduction of supplementary pension schemes will not automatically provide remedies for deficiencies and problems of the public pension schemes. Furthermore, different effects on the economy will occur in different institutional and cultural environments. Therefore taking some pension provision models as an example (as often is the case) might not give the expected results.